Eficácia e vias de transferência de inseticidas no controle de Euschistus heros (Fabricius, 1798) (Hemiptera: Pentatomidae) - Cavallin, Lucas de Arruda (2020)
The neotropical brown stink bug, Euschistus heros (Fabricius, 1798) (Hemiptera: Pentatomidae), is considered the main soybean pest in Brazil. This study presents two manuscripts that aim to understand the efficacy of insecticides, how insecticides contamination occurs, and which are the most important transfer mode of insecticides for mortality of E. heros. The first research entitled "Efficacy of insecticides in the control of Euschistus heros (Fabricius, 1798) (Hemiptera: Pentatomidae) in soybeans, in two edaphoclimatic regions of Rio Grande do Sul" found that the control efficacy of nymphs in Santa Maria ranged between 29,6% and 77.3%, and of adults ranged between 66.2% and 92.3%. In Capão do Cipó locality, the control of E. heros varied between 45.4% and 77.3%. The best efficacy was accomplished by Curbix + Evidance (500 mL + 143 g ha-¹) and Orthene (1000 g ha-¹) in both locations. In Santa Maria locality, Expedition (300 mL ha-¹), Engeo Pleno S (250 mL ha-¹), Sperto (250 mL ha-¹) and Galil (400 mL ha-¹) were the most effective. The second manuscript entitled "Insecticide transfer mode in Euschistus heros (Fabricius, 1798) (Hemiptera: Pentatomidae)", found differences in susceptibility among E. heros populations, depending on the via of insecticides transferring. Insecticide transferred via topical contact, tarsal contact and via ingestion were effective in the control of E. heros, however, it differs with the type of insecticide. Mortality of E. heros based on the via of respiratory system was extremely low, varying between 10.0% and 21.7%. The mortality of E. heros via ingestion was highly dependent of the treatment and ranged between 8% and 91.3%. However, the mortality via topical contact, tarsal contact and tarsal contact + ingestion was up to 100%. Therefore, understanding the effectiveness and via of insecticide transferring into E. heros, provides support to make the best decisions in the field, and to ensure an effective control of E. heros in soybeans.